The Effect of Goat Milk Fractions Supplementation on Serum IgE Response and Leukocytes Count in Dinitrochlorobenzene Sensitized Rat - Nurliyani, Nurliyani (2012)
In Indonesia, goat milk is often consumed and believed as anti-allergy. The objective of this research was to study the effect of goat milk and their fractions (casein and whey) supplementation on total serum IgE concentrations and leukocytes count in rat sensitized with contact allergen dinitrocholorobenzene (DNCB)> Female Wistar rats 6-8 weeks old were divided into four grups: 1) whey, 2) casein, 3) whole milk supplementation, 4) phosphate-bufferedsaline/PBS (control). The results showed that supplementation of goat milk on rats did not affects on total serum IgE concentrations and number of leukocytes. After sensitized with DNCB, the monocyte percentage in rats was higher (P<0.01) that before. In conclusion, goat milk or their fractions supplementation unable to decrease the total serum IgE concentration and also had no effect on leukocyte count. However, 1% DNCB could increase the number of monocytes, but could not induce the IgE response.